Survival of current production tumor endoprostheses: Complications, functional results, and a comparative statistical analysis. Issue 6 (4th September 2013) - Pala, E.; Henderson, E.R.; Calabrò, T.; Angelini, A.; Abati, C.N.; Trovarelli, G.; Ruggieri, P.
Abstract Background and Objectives Retrospectively analyze outcomes of current‐generation Global Modular Replacement System (GMRS) modular tumor endoprosthesis for the lower limb in primary and secondary implantation procedures. Methods Two hundred ninety five prostheses were implanted, 197 were primary implants, 98 were for revision surgery; revision procedures included 84 failed tumor reconstructions and 14 failed non‐tumor reconstructions. Anatomic sites included: distal femur 199; proximal tibia 60; proximal femur 32;total femur 4. Endoprosthesis failures were classified as soft‐tissue failures (Type 1), aseptic loosening (Type 2), structural fracture (Type 3), infection (Type 4), and tumor recurrence (Type 5). MSTS functional scores were measured. Results The overall failure rate was 28.8% and failure occurred at a median of 1.7 years (range, 1 month to 7 years). At a mean oncologic follow up of 4.2 years (range, 2–8 years), 195 patients are continuously NED, 43 NED after treatment of relapse, 10 AWD, 33 DWD. There was a significant difference in implant survival of all modes of failure between primary and revision implants (P = 0.03). No prosthetic fracture occurred. The average functional score was 81.6% (24.5). Conclusions Mid‐term results with GMRS are promising, with good functional results and low incidence of complications for primary implants. Level of Evidence Therapeutic study, level IV‐1 (case series). J. Surg. Oncol. 2013; 108:403–408. © 2013 Wiley Periodicals, Inc.